2022
DOI: 10.1177/00220345221088527
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Head and Neck Cancer Pain

Abstract: Head and neck cancer (HNC) affects over 890,000 people annually worldwide and has a mortality rate of 50%. Aside from poor survival, HNC pain impairs eating, drinking, and talking in patients, severely reducing quality of life. Different pain phenotype in patients (allodynia, hyperalgesia, and spontaneous pain) results from a combination of anatomical, histopathological, and molecular differences between cancers. Poor pathologic features (e.g., perineural invasion, lymph node metastasis) are associated with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 63 publications
2
21
1
Order By: Relevance
“…One reason might be the regulation of tumor immunology by neurons (Scheff et al 2022, Udit et al 2022). Given that pain is a prognostic factor for survival (Reyes-Gibby et al 2014), it suggests shared mechanisms linking carcinogenesis and pain in HNSCC (Ye et al 2022). Our present work shows that sEVs released by cancer cells are a key mediator of communication to TRPV1+ neurons in line with previous reports (Madeo et al 2018, Vermeer 2019, Amit et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason might be the regulation of tumor immunology by neurons (Scheff et al 2022, Udit et al 2022). Given that pain is a prognostic factor for survival (Reyes-Gibby et al 2014), it suggests shared mechanisms linking carcinogenesis and pain in HNSCC (Ye et al 2022). Our present work shows that sEVs released by cancer cells are a key mediator of communication to TRPV1+ neurons in line with previous reports (Madeo et al 2018, Vermeer 2019, Amit et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of ATF3 in neurons following exposure to isolated sEVs further supports this hypothesis. ATF3 is classically upregulated after nerve injury, TRPV1 activation, and is associated with transcriptional reprogramming necessary for peripheral nerve regeneration and neuropathic pain (Tsujino et al 2000, Bráz et al 2010, Renthal et al 2020), suggesting that cancer pain has a neuropathic component (Ye et al 2022). The upregulation of ATF3 in response to sEVs supports the idea that sEVs drastically impact the neuronal gene expression to switch to a transcriptome facilitating axon elongation and neuronal sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48,50,74] Schwann cells are also involved in cancer pain. [12,16,25,44,45,69,70] In the present study, we hypothesize that SCs can promote oral cancer cell aggressiveness. We quantified OSCC cell proliferation, invasion, morphology, and metabolism in the presence of SCs.…”
Section: Introductionmentioning
confidence: 69%
“…Since SCs have been implicated in cancer metastasis, [74] and pain, [12,16,25,44,45,69,70] we asked whether there are a set of common cancer genes that regulate both metastasis and pain that could be affected by the presence of SCs. In a recent RNAsequencing study conducted at NYU Oral Cancer Center, a total of 40 upregulated DEGs were found to be associated with both nodal metastasis and pain in oral cancer patients.…”
Section: Scs Alter the Expression Of Genes Associated With Metastasis...mentioning
confidence: 99%